The EPPO/OLAF compendium of national procedures: Germany - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Krause-Ablaß, Anna-Elisabeth; Justus Liebig University Giessen (My University, 2026)
This German EPPO/OLAF volume opens with Prof. Hauck’s and European Delegated Prosecutor Krause-Ablaß' review of EPPO activities in the past two years and suggestions for optimisation. It then leads the reader to a compilation of German and Union laws (EPPO/OLAF Regulations) on fraud (PIF) offences and irregularities. The working methods of the EPPO (EUStA) regional offices (discontinuation or indictment, types of offences, RiStBV, MiStrA, examples) can also be found in the volume. It discusses the role of the EPPO in the fight against fraud, summarising the relevant laws and current case law on fraud. The handbook also contains information and guidelines for defence lawyers in cases of tax or subsidy fraud. In addition, the volume provides an introduction to OLAF’s national measures. EDP Dr Anna-Elisabeth Krause-Ablaß has acted as the publication’s national expert.
Keywords: ddc:340; ddc:320